Force-spectrum relations for molecular optical force probes - Neudecker, Tim; Dreuw, Andreas (Angewandte Chemie. International edition, 2014)
Force probes allow real-time monitoring of forces acting in different regions of large molecules and are potentially suited for the investigation of structural changes occurring in macromolecules during, e. g., folding processes.1-10 Such information is crucial for the understanding of mechanochemical reactivity.2, 3, 6, 7 To this end, small molecular force probes can be incorporated into large molecules.2, 3, 11-13 Some of the available systems are based on mechanochromism, the change of the UV/Vis absorption spectrum of a molecule under mechanical stress.1, 14 Herein we propose the idea of using molecular force probes in which the point-group symmetry is reduced as a result of mechanical deformation. This effect leads to significant and characteristic changes in the UV/Vis, IR, and Raman spectra of the deformed molecules, which were determined using computational methods. Beneficially, these changes are reversible and occur even if the applied forces are small.
Gesehen am 15.12.2017